LEGAL REGULATION OF THE TERRITORIAL RECRUITMENT AND SOCIAL SUPPORT CENTERS ACTIVITIES IN THE CONTEXT OF IMPROVING MILITARY LEGISLATION OF UKRAINE - Mykulets, Vitalii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the analysis of the legal regulation of the territorial recruitment and social support centers activities in order to determine directions for improving their legal status was conducted. Research methods: general theoretical and analytical methods combined with systemic and complex approaches. Results: it was determined that at the theoretical level of the study that the creation of a new body of state power based on the existing system of the territorial recruitment and social support centers with the simultaneous adoption of a special law will contribute to the improvement of the legal regulation of the activities of these territorial centers and, at the same time, the appearance of such a law would become an important element of the improvement of the military legislation of Ukraine. The idea is argued that the proposed reform of the system of territorial recruitment and social support centers will contribute to a positive transformation of the attitude of citizens towards these territorial centers, and will also be a confirmation of the legal nature of the Ukrainian state. Discussion: the issue of non-compliance of the status of territorial recruitment and social support centers with their real functional load is raised. It is proven that, in accordance with the current legislation, it is expedient to transform the system of the territorial recruitment and social support centers into a state service whose activities are directed and coordinated by the Cabinet of Ministers of Ukraine through the Minister of Defense, and which implements state policy in the areas of military duty and military service, mobilization training and mobilization, and social support. The author emphasized that it is necessary to develop and adopt a specific law in order to ensure the legal nature of the activity of such a service.